Incentivizing demand for supply-constrained care: institutional birth in India - Andrew, A; Vera-Hernández, M (MIT Press, 2024)
If overcrowding harms healthcare quality, the impacts of encouraging more people to use services are not obvious. Impacts will depend on whether marginal entrants benefit and whether they benefit enough to offset the congestion externalities imposed on inframarginal users. We develop a general-equilibrium model that formalizes these ideas. We examine them empirically by studying JSY, a program in India that paid women to give birth in medical facilities. We find evidence that JSY increased perinatal mortality in areas with low health-system capacity, particularly harmed more-complex births, reduced the quality of facilities' postnatal care, and generated harmful spillovers onto other services.